A foreign body of the larynx misdiagnosed as vocal cord paralysis. (12th July 2013) - Kumar, Sunil; Singh, Devendra Bahadur; Singh, Abhishek Bahadur
Abstract : Foreign bodies in the aerodigestive tract continue to be a common problem that contribute significantly to high morbidity and mortality all over the world. Laryngeal foreign bodies may present with less severe symptoms compared with lower respiratory tract foreign bodies, resulting in misdiagnosis, confusion and delay in diagnosis. Rigid endoscopy with forceps removal under general anaesthesia is the preferred management modality. This case is described to show the importance of a detailed history and examination including X-ray neck in children to rule out any radiopaque laryngeal foreign body as a delay in diagnosis and management can lead to life-threatening complications.